Toward a framework for automated service composition and execution - Pathathai Na-Lumpoon (2018)
© 2014 IEEE. Service composition brings many benefits of reusing existing services (so called components) to synthesize a new resulting service (so called composite). Composing a service composition usually happens at design time, but this limit the choices of component services. This paper presents a framework for web service composition and execution based on the integration of different domains. Given a user's query, and a list of service descriptions (in SAWSDL), the framework first provides an automated composition of services based on Fluent Calculus. This step, employing chaining inference from AI-planning with FLUX constraint programming method, generates a plan which is either a sequence or a parallel composition of operations offered by the selected services. As a second step, the plan is transformed into a BPMN (Business Process Modeling Notation) model in order to be executed by any BPMN engine. The proposed work relies on a broad project that aims at design and develop a non intrusive framework dediated to context aware mobile services [1]-[3].